Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/jmri.21852
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility effects in hyperpolarized 3He lung MRI at 1.5T and 3T

Abstract: Purpose:To compare susceptibility effects in hyperpolarized 3 He lung MRI at the clinically relevant field strengths of 1.5T and 3T. Materials and Methods:Susceptibility-related B 0 inhomogeneity was evaluated on a macroscopic scale by B 0 field mapping via phase difference. Subpixel susceptibility effects were quantified by mapping T * 2 . Comparison was made between ventilation images obtained from the same volunteers at both field strengths. Results:The B 0 maps at 3T show enhanced off-resonance effects cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(75 citation statements)
references
References 18 publications
7
68
0
Order By: Relevance
“…The relatively long transverse relaxation time ( normalT2*) of 129 Xe in the gas phase ( normalT2* = 52 ± 20 ms at 1.5T) compared to 3 He ( normalT2* = 27.8 ± 1.2 ms at 1.5T) allows the use of longer readout times per interleave, fewer radiofrequency (RF) pulses, and larger flip angles . The use of fewer interleaves allows for rapid coverage of the whole of k‐space, resulting in higher temporal resolution in dynamic gas ventilation imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively long transverse relaxation time ( normalT2*) of 129 Xe in the gas phase ( normalT2* = 52 ± 20 ms at 1.5T) compared to 3 He ( normalT2* = 27.8 ± 1.2 ms at 1.5T) allows the use of longer readout times per interleave, fewer radiofrequency (RF) pulses, and larger flip angles . The use of fewer interleaves allows for rapid coverage of the whole of k‐space, resulting in higher temporal resolution in dynamic gas ventilation imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Although authors of another study (20) have experimentally verified that the signal-to-noise ratio is independent of field strength in the 1.5-T and 3-T systems used in this study, differences in T2* effects were observed. A 3.3%-7.7% signal loss is expected at 3 T compared with that at 1.5 T at our acquisition parameters on the basis of published values of T2* (20,21). This small signal loss would most likely not affect a human reader, but it may be sufficiently large that a fully automated approach would require some level of intersite calibration for consistent results.…”
Section: Discussionmentioning
confidence: 75%
“…By acquiring VDP/ T 2 */ADC/morphometry estimates during a single 3 He scan, we eliminate the need for two separate static‐ventilation and diffusion‐weighted scans. The 3 He T 2 *‐results suggested that T 2 * values were in the 7–9 msec interval for severe emphysema patients; 3 He MRI T 2 * values have previously been measured in young healthy volunteers on 3 T GE (7 ± 1.4 msec) and Philips (10.8 ± 1.8 msec) MRI systems . The mean T 2 * values we reported were in the same range (7–9 msec), and therefore, the free induction decay estimates we generated were likely physiologically realistic for the age and disease status of the participants in this study.…”
Section: Discussionmentioning
confidence: 77%